EVALUATION OF GROUNDWATER QUALITY FOR SUSTAINABLE DRINKING AND IRRIGATION (International Journal of Food and Nutritional Sciences, 2021)
The detection and management of groundwater quality play a critical role in the preservation of freshwater resources in arid and semi-arid environments, which is essential for sustainable development. The allocation of resources between agricultural and drinking uses may be determined by local authorities and water resource managers based on the quality of groundwater in various locations. This research aims to identify areas in the Tabriz aquifer, located in the northwest Iranian province of East Azerbaijan, where water pumping is suitable for harvesting and drinking. Data on electrical conductivity (EC), total dissolved solids (TDS), calcium (Ca), magnesium (Mg), sodium (Na), potassium (K), sulphate (SO4), total hardness (TH), bicarbonate (HCO3), pH, carbonate (CO3), and sodium adsorption ratio (SAR) were gathered from 39 wells between 2003 and 2014 and used in a groundwater compatibility study. The Water Quality Index (WQI) and Irrigation Water Quality (IWQ) indices are employed in tandem with one another because of their mutually reinforcing relevance in assessing the quality of water resources for drinking and irrigation. The WQI index was used to categorise drinking water into three zones: excellent, good, and terrible. The majority of drinking water collected for use in urban and rural areas is deemed to be "excellent water" or "good water," according to the study.